Fundamental investigation on influence of external heat on chip formation during thermal assisted machining - Alkali, A.U. (Institute of Physics Publishing, 2018)
Various heat sources have been investigated by numerous researchers to reveal machinability benefits of thermally assisted machining (TAM) process. Fewer engineering materials have been tested. In the same vein, those researches continue to demonstrate effective performance of TAM in terms of bulk material removal rate, improved surface finish, prolong tool life and reduction of cutting forces among others. Experimental investigation on the strain-hardenability and flow stress of material removed with respect to increase in temperature in TAM has not been given attention in previous studies. This study investigated the pattern of chip morphology and segmentation giving close attention to influence of external heat source responsible for strain - hardenability of the material removed during TAM and dry machining at room temperature. Full immersion down cut milling was used throughout the machining conditions. Machining was conducted on AISI 316L using uncoated tungsten carbide end mill insert at varying cutting speeds (V) of 50, 79, and 100 m/min, and feed rates (f) of 0.15, 0.25, and 0.4 mm/tooth while the depth of cut was maintained at 0.2mm throughout the machining trials. The analyses of chip formation, segmentations and stain hardenability were carried out by using LMU light microscope, field emission microscopy and micro indentation. The study observed that build up edge is formed when a stagnation zone develops in front of tool tip which give rise to poor thermal gradient for conduction heat to be transferred within the bulk material during dry machining. This promotes varying strain - hardening of the material removed with evident high chips hardness and thickness, whereas TAM circumvents such impairment by softening the shear zone through local preheat. Â© Published under licence by IOP Publishing Ltd.